2022
DOI: 10.48550/arxiv.2202.12938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the State of Self-Supervised Human Activity Recognition using Wearables

Abstract: The emergence of self-supervised learning in the field of wearables-based human activity recognition (HAR) has opened up opportunities to tackle the most pressing challenges in the field, namely to exploit unlabeled data to derive reliable recognition systems from only small amounts of labeled training samples. Furthermore, self-supervised methods enable a host of new application domains such as, for example, domain adaptation and transfer across sensor positions, activities etc. As such, self-supervision, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In recent years, self-supervised learning (SSL) approaches have gained attention as a general framework for learning from unlabeled data through a pretext task [5], [32]. SSL has also been applied to sensor-based HAR, leading to promising results [33], [34]. However, even a good unsupervised or SSL model that permits adaptation using a short amount of data still requires a significant amount of data, as exemplified in other domains such as vision and speech [35].…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, self-supervised learning (SSL) approaches have gained attention as a general framework for learning from unlabeled data through a pretext task [5], [32]. SSL has also been applied to sensor-based HAR, leading to promising results [33], [34]. However, even a good unsupervised or SSL model that permits adaptation using a short amount of data still requires a significant amount of data, as exemplified in other domains such as vision and speech [35].…”
Section: Related Workmentioning
confidence: 99%
“…Modeling the heterogeneous PD symptoms is challenging and we could be better served modeling the physiological patterns of healthy subjects instead. The validity of our approach has been corroborated in recent work [361] which benchmarked the various self-supervised learning algorithms when used on the task of activity recognition. Haresamudram et al [361] found that increasing the number of participants intuitively improves downstream performance.…”
Section: Discussionmentioning
confidence: 60%
“…The validity of our approach has been corroborated in recent work [361] which benchmarked the various self-supervised learning algorithms when used on the task of activity recognition. Haresamudram et al [361] found that increasing the number of participants intuitively improves downstream performance. However, the gains quickly saturate with no significant difference between using 25% and 100% of participants.…”
Section: Discussionmentioning
confidence: 60%